Optimizing the application strategy of phosphorus fertilizer by Pseudomonas E sp017968885 to increase phosphorus yield of pepper - Hu, Qinqin; Wu, Hongyan; Yu, Miao; Song, Liqun; Feng, Jian; Ma, Yan; Ding, Fucheng; Guo, Lingling; Wang, Zhixue (Frontiers in Agronomy, 2025)
IntroductionThis study aimed to evaluate the ability of Pseudomonas E sp017968885 to mobilize insoluble phosphate under different phosphorus (P) fertilizer application rates, as well as its impacts on soil properties and pepper yield—providing insights for optimizing P fertilizer application strategies in sustainable agriculture.MethodsA pot experiment was conducted, consisting of six treatments: five inoculated groups (P1+H50 to P5+H50) treated with varying P fertilizer rates (1.17~1.96 g/pot) and one non-inoculated group (Control) as the reference. Key soil and crop indicators, along with microbial gene expression, were measured to assess the strain’s effects.ResultsAt the fruit setting stage, the content of Olsen-P (available phosphorus) in the P1+H50 to P3+H50 treatments increased by 66.36~102.08% compared with the Control, with a significant difference (P<0.05). The P2+H50 treatment significantly enhanced the activity of soil acid phosphatase (S-ACP) by 16.79% relative to the Control (P<0.05). Pepper P uptake in the inoculated treatments increased by 32.67~84.06% (P<0.05), which was correlated with a 23.98~65.80% increase in yield compared with the Control (P<0.05). The expression of phosphate-solubilizing ability-related genes (e.g., pqq, gdh) supported the observed changes in P-related physicochemical indicators. Additionally, Pseudomonas E sp017968885 exhibited genetic potential in secondary metabolite synthesis, protein secretion, and siderophore production—providing a molecular basis for its advantages in environmental adaptation and ecological competition.DiscussionThese findings confirm that Pseudomonas E sp017968885 is a promising biofertilizer. It can reduce external P input while improving crop productivity by enhancing nutrient cycling, which is of great significance for promoting sustainable agricultural development.